2021
DOI: 10.3390/su14010189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Pollution in the Sustainability of Architectural Heritage: Case Study from Cartagena of India, Colombia

Abstract: Limited studies have been carried out in emerging nations on the correlation among the environmental pollution, economic factors, and architectural heritage. For this reason, this research presents an assessment of environmental parameter values on materials deterioration used in architectural heritage in Cartagena de Indias; furthermore, it depicts the effect of heritage degradation on socioeconomic aspects of people whose livelihood depends on trade, tourism, and service activities. Dose-response functions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…This resin uses propylene as its raw material for its synthesis, which requires a high degree of purity to avoid interference in the process [ 12 , 17 , 18 ]. Studies have shown that the impurities present in the propylene can affect the properties of the synthesized resin, causing the production of resin outside of specifications that becomes waste, generating more pollution, or producing resin that must be processed, generating a high consumption of energy and other raw materials to reach the desired quality [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This resin uses propylene as its raw material for its synthesis, which requires a high degree of purity to avoid interference in the process [ 12 , 17 , 18 ]. Studies have shown that the impurities present in the propylene can affect the properties of the synthesized resin, causing the production of resin outside of specifications that becomes waste, generating more pollution, or producing resin that must be processed, generating a high consumption of energy and other raw materials to reach the desired quality [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combustion of coal and other fossil fuels, vehicular traffic, and various other industrial emissions result in atmospheric pollution from sulphur dioxide (SO 2 ), particulate matter (PM), and numerous other gaseous (e.g., NO x , CO 2 , H 2 S, and HCl) and dusty components [2][3][4]. As a result, stone surfaces exposed over long periods gradually darken due to the accumulation of pollutants, particularly carbonaceous particles [5][6][7][8][9]. Consequently, these surfaces become coated with thin black layers and/or so-called soiling [10].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the survey method and the algorithm of data fusion, it can be seen from the research results of the survey method that human exploration of regional culture has never stopped. The literature [27] evaluated the values of environmental parameters for the degradation of materials used in the architectural heritage of Cartagena de India. In addition, it describes the impact of heritage degradation on the socio-economic aspects of people whose livelihoods depend on trade, tourism and service activities.…”
Section: Introductionmentioning
confidence: 99%